Rencana Aksi Nasional Memerangi Sampah Laut Sebagai Bentuk Implementasi Sdgs 14: Kehidupan Di Bawah Laut - Saurandri Putri Cahyati; Shifa Melinda Naf’an; Nanda Iris Savana; Yusin Noviarin (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Marine debris is a problem that rises to global and national urgency, given the fact that Indonesia is the second largest contributor of plastic waste to the world after China. The author tries to examine Indonesia’s national action plan on marine debris and the policy as a driver in the implementation of SDGs no. 14. In answering these problems, the authors use descriptive qualitative method by describing the previously collected data which are then arranged to systematically discuss. The article finds that the national action plan is considered an initiative in stemming Indonesia’s concerns on the problem of plastic waste. This article also finds that this program cannot be said to be effective because there are several aspects that need to be reviewed; however, it can be said to be effective when assessed in the context of Indonesia’s compliance with the international maritime regime.